Climate Models - Druyan, Leonard M. (IntechOpen, 2012)
Climate Models offers a sampling of cutting edge research contributed by an international roster of scientists. The studies strive to improve our understanding of the physical environment for life on this planet. Each of the 14 essays presents a description of recent advances in methodologies for computer-based simulation of environmental variability. Subjects range from planetary-scale phenomena to regional ecology, from impacts of air pollution to the factors influencing floods and heat waves. The discerning reader will be rewarded with new insights concerning modern techniques for the investigation of the natural world.